Study on Movement Law of High-Position Thick and Hard Roof and Mine Earthquake Control by Ground Fracturing Technology. (29th June 2022) - Liang, Yanbo; Cheng, Yuanfang; Han, Zhongying; Yan, Chuanliang; Zhang, Xiufeng; Wang, Chao; Han, Songcai
Abstract : The field monitoring data showed that the fracture of high-position thick and hard roof (THR) was the main reason for the frequent occurrence of high-energy mine earthquake events (magnitude > 2.0 ) in the no. 6 mining district of Dongtan coal mine. In order to study the fracture characteristics of high-level THR and seek a reasonable and effective control method, taking the 63up 06 working face as the engineering background, the FLAC model was built to simulate the strata movement law before and after fracturing. The simulation results showed that the THR first breaking span was 340 m, the tensile failure runs through the whole THR, and the subsidence increased rapidly when THR reached the first breaking span. The THR breakage is related to the continuous upward transfer of horizontal compressive stress, which results in the concentration of horizontal compressive stress in THR. After ground fracturing, the first breaking span of THR decreased, and different fracturing positions have a great impact on the THR fracture form. When the fracturing position is close to the center of the first breaking span, there is no large cantilever breaking form in the THR, the THR breaks on both sides of the top and sinks along the hydraulic fracture in the middle, and the collapse degree is relatively uniform. Then, the fracturing test was carried out in the 63up 06 working face, the results showed that during the first 400 m of the 63up 06 working face mining after fracturing, 702 microseismic events occurred in total, including 12 high-energy vibration events which include 4 mine earthquakes of magnitude 2.0 and 8 mine earthquakes of magnitude 1.0-2.0. Compared with the adjacent working face, the quantity of high-energy mine earthquake events in the 63up 06 working face has been significantly controlled.